An Au(I)-based coordination/hydrogen-bond hybrid open framework for luminescence sensing of temperature and benzene - Wang, Hao-Yu; Ye, Jia-Wen; Zhang, Xue-Wen; Wang, Chao; Lin, Duo-Yu; Zhou, Dong-Dong; Zhang, Jie-Peng (Science bulletin, 2022)
[Display omitted]